###### Advertisements

###### Advertisements

Simplify :-

`2^(2/3).2^(1/5)`

###### Advertisements

#### Solution

`2^(2/3).2^(1/5) = 2^(1/3+1/5) = 2^((10+3)/15) = 2^(13/15)`

#### APPEARS IN

#### RELATED QUESTIONS

Prove that:

`1/(1+x^(b-a)+x^(c-a))+1/(1+x^(a-b)+x^(c-b))+1/(1+x^(b-c)+x^(a-c))=1`

Prove that:

`(a^-1+b^-1)^-1=(ab)/(a+b)`

Simplify the following:

`(3^nxx9^(n+1))/(3^(n-1)xx9^(n-1))`

Solve the following equation for x:

`2^(x+1)=4^(x-3)`

Assuming that x, y, z are positive real numbers, simplify the following:

`(x^((-2)/3)y^((-1)/2))^2`

Find the value of x in the following:

`2^(5x)div2x=root5(2^20)`

Write the value of \[\left\{ 5( 8^{1/3} + {27}^{1/3} )^3 \right\}^{1/4} . \]

If (x − 1)^{3} = 8, What is the value of (x + 1)^{2} ?

Which of the following is (are) not equal to \[\left\{ \left( \frac{5}{6} \right)^{1/5} \right\}^{- 1/6}\] ?

The value of \[\sqrt{5 + 2\sqrt{6}}\] is